A meta-analysis of the efficiency of metal nanoparticles in vaccine delivery against infectious disease - Hoseini, Zakieh Sadat; Hajizade, Abbas; Easton, Andrew J; Ahmadian, Gholamreza; Ramezani, Fatemeh (Nanomedicine, 2021)
Exploration of the efficiency of metal nanoparticles as adjuvants have reported varying results. The efficacy of metal nanoparticles as adjuvants was investigated Database were searched using the terms ‘metal nanoparticles’ and ‘vaccines’. Studies in animal models utilizing any metal-based vaccines, where the survival rate was described. The quality of the studies was examined using aspects of the ARRIVE guidelines and assessment of the risk of bias of included studies. Metal nanoparticle-based adjuvants were more effective compared with control (unvaccinated groups) but have not been more successful in competing with common adjuvants or even antigens alone. More than 75% of articles have used only gold nanoparticles. Nano-adjuvants do not have a significant effect on reducing mortality.